Rivers help us to quantify the socio-ecological functioning of their basin at the Anthropocene: the Seine example (1850–2020) - Meybeck, Michel; Bouleau, Gabrielle; Carré, Catherine; Garnier, Josette; Lestel, Laurence (Comptes Rendus. Géoscience)
River basins were identified very early on as a key component of chemical fluxes from continents to oceans, driven by weathering and biogeochemical cycles in their basin. Fifty years ago, important riverine changes attributed to human impacts started to be studied at the global scale, an evolution which has been the foundation for Anthropocene studies in hydrosystems since 2000. However, the co-evolution of river basin systems and sociosystems remains poorly addressed, particularly over long periods ($>$100 y). Medium-sized river basins make it possible to perform such detailed analyses, which combines historical river fluxes, material flows, river ecology, environmental history and political ecology.Such an interdisciplinary approach at the scale of the Seine basin, undertaken by the PIREN-Seine research program, started in 1989, has shown how scientific and technological knowledge, environmental awareness, environmental regulations and policies, and political decisions have played a role on water quality during that period.